Sclerotherapy – A novel modality in the management of oral pyogenic granuloma - Abhishek Govind Soni (Journal of Indian Society of Periodontology, 2021)
Pyogenic granuloma is a commonly occurring inflammatory hyperplasia involving the oral cavity. Surgical resection of the lesion is the mainstay treatment of pyogenic granuloma. However, intraoperative bleeding, postoperative infection, and recurrence chances are more with the surgical technique. Therefore, sclerotherapy has evolved as an effective alternative approach, which is simple, noninvasive, with minimal discomfort to the patient and having little recurrences and few complications. This case report is an attempt to highlight the usefulness of sclerotherapy procedure in the management of orogingival pyogenic granuloma, particularly involving the anterior esthetic zone of the oral cavity.